Trends and inequality of human resource in centers for disease control and prevention in China from 2019 to 2023 - Zhang, Na; Wu, Qiong; Li, Shaoqiong; Wang, Chongyi; Mao, Ayan; Guo, Qing; Qiu, Wuqi (Frontiers in Public Health, 2025)
BackgroundThe public health workforce plays a crucial role in the development of health systems, particularly in enhancing the capacity of public health infrastructure. Understanding the current status of human resources in the Centers for Disease Control and Prevention (CDC) is essential for establishing future development goals. This study aims to assess the quantity and equity of the human resources in China’s CDCs since the outbreak of COVID-19, with the goal of promoting a more equitable distribution of the CDC workforce and enhancing the capacity to respond effectively to major public health emergencies.MethodsUsing nationwide administrative data from China CDC (2019–2023), we conducted a two-stage analysis: First, we conducted a descriptive analysis of the current status and trends of the CDC workforce. Second, we performed an equity assessment through multilevel decomposition (1) Calculated Gini coefficients across three dimensions (geography, Gross Domestic Product per capita, population density); (2) Applied Theil T/L index to partition inequalities into within-region and between-region components.ResultsBetween 2019 and 2023, the CDC workforce in China increased to 230,594 employees, with workforce density rising from 1.3 to 1.64 per 10,000 residents, 76.26% being health professionals, a majority of whom were female, and the 25–34 age group comprising the largest segment (29.06%). Additionally, while the proportion with less than 5 years of service grew, staff with over 30 years of service formed the largest tenure group (30.69%). The Gini coefficient revealed extreme spatial inequality, indicating that geographic distribution was significantly exceeding those based on economic and population distributions, with values of 0.5815, 0.3866, and 0.1843, respectively, in 2023. Decomposition of inequality indicated that both general staff and health professionals were primarily affected by within-region disparities, with an increasing trend of within-region inequity from 2019 to 2023. In 2023, Theil T analysis showed that within-region inequality accounted for 76.67% of staff disparities, while for health professionals, this figure was 64.21%.ConclusionThe human resource landscape in China’s CDCs faces challenges related to both underfunding and an aging workforce. Inequities in workforce distribution persisted from 2019 to 2023, with significant disparities within regions. Strengthening the CDC workforce, particularly in underdeveloped and sparsely populated areas, is essential for addressing these challenges.